DEVELOPING CREATIVITY IN STUDENTS THROUGH THE LIFE AND WORK OF BOTIR ZAKIROV - Kabilova E.B. (Galaxy International Interdisciplinary Research Journal, 2024)
There is a lot of attention in the field of music and art in our country. At the same time as the modern pop performance is developing, in my opinion, the interest of young people in light popular music and songs is increasing. I think it is important to present and introduce many conversations, concerts, auditions about the life and creative path of real artists and singers. In this article, the development of pop art in Uzbekistan is important The development of creativity in students through the life and work of B.Zokirov, who contributed and laid the foundation stone of pop performance, was discussed and conclusions were presented.